Risk Factors for Stiff Left Atrial Physiology 1 Year After Catheter Ablation of Atrial Fibrillation - Jae-Hyuk Lee; Oh-Seok Kwon; Hee Tae Yu; Tae-Hoon Kim; Jae-Sun Uhm; Boyoung Joung; Moon-Hyoung Lee; Hui-Nam Pak (Frontiers in Physiology, 2021)
Catheter ablation is the most effective rhythm control method for patients with atrial fibrillation (AF); however, it inevitably causes atrial tissue damage. We previously reported that AF catheter ablation (AFCA) increases left atrial (LA) pressure without changes in symptom scores. We hypothesized that extensive LA ablation increased the risk of stiff LA physiology. We included 1,720 patients (69.1% male, 60.0 [53.0–68.0] years old, 66.2% with paroxysmal AF) who underwent de novo AFCA and echocardiography before and 1-year after the procedure. Stiff LA physiology was defined, when the amount of the estimated pulmonary arterial pressure increase between the pre-procedural and the 1-year post-procedural follow-up echocardiography was >10 mmHg and when right ventricular systolic pressure (RVSP) was >35 mmHg at 1-year follow-up echocardiography. The failed rhythm control within 1 year was defined as recurrent AF despite using anti-arrhythmic drugs or cardioversion within a year of AFCA. We explored the incidence and risk factors for stiff LA physiology and the rhythm outcome of AFCA. Among the 1,720 patients, 64 (3.7%) had stiff LA physiology 1 year after AFCA. Stiff LA physiology was independently associated with diabetes (odds ratio [OR], 2.36 [95% CI, 1.14–4.87], p = 0.020), the ratio of the peak mitral flow velocity of the early rapid filling to the early diastolic velocity of the mitral annulus (E/Em; OR, 1.04 [95% CI, 1.00–1.10], p = 0.049), LA pulse pressure (Model 2: OR, 1.05 [95% CI, 1.00–1.11], p = 0.049), low LA voltage (OR, 0.36 [95% CI, 0.18–0.74], p = 0.005), empirical extra-pulmonary vein (PV) LA ablation (OR, 2.60 [95% CI, 1.17–5.74], p = 0.018), and radiofrequency (RF) ablation duration (Model 2: OR, 1.02 [95% CI, 1.01–1.03], p = 0.003). Although the incidence of post-AFCA stiff LA physiology was 3.7% and most of the cases were subclinical, the empirical extra-PV ablation was associated with this undesirable condition. In addition, patients who had low mean LA voltage before AFCA could be susceptible to stiff LA physiology.